Hubungan antara Kandungan Bahan Organik Tanah dengan Periode Pasca Tebang Tanaman HTI Acacia Mangium Willd. - Sabaruddin Sabaruddin; Siti Nurul Aidil Fitri; Lesi Lestari (UNIVERSITY OF LAMPUNG, 2009)
Relationship between the Organic Matter Content with Post Harvest Period of Forest Industrial Plant Acacia mangium Willd (Sabaruddin, S.N.A. Fitri, and L. Lestari): Timber harvesting may have significant effects on soil organic matter content through mechanical disturbance, inputs of logging slash, alterations in litter production, and leaching of dissolved organic matter, as well as the alteration of temperature and moisture regimes. To investigate the effect of post-harvest period of tree harvesting on the dynamics of soil organic matter content, surface soils (0 to 10 cm and 10 to 20 cm) were collected from intact Acacia mangium Willd. plantation (control) and from A. mangium Willd. harvested in 2001, 2002, 2004, and 2006 in four replicates. Each replicate consisted of composited 4 sub-samples. Timber harvesting reduced litter accumulation on soil surface. However, the amount of litter accumulated on soil surface increased as post-harvest period increased. Timber harvesting significantly (p<0.001) affected soil organic matter content both in 0 to 10 cm and 10 to 20 cm. The increases in soil organic matter content were significantly correlated (r=0.85; p<0.001 in 0 to10 cm and r=0.62; p<0.01 in 10 to 20 cm) with post harvest period.